Development and substantiation of an improved version of a main drainage facility classical scheme at a kimberlite mine developed by block caving method - Nickolay P. Ovchinnikov (Горные науки и технологии, 2023)
Evidence demonstrates that as the production capacity of a kimberlite mine increases, there is a corresponding increase in the volumetric concentration of suspended solids in the mine water extracted from its watercollecting workings. The Udachny mine, known for its high productivity in comparison to other domestic kimberlite mines, experiences a higher concentration of suspended solids in the mine waters, leading to significant sludge settling within the primary drainage facility’s water-collecting workings. This determinal effect adversely affects the operational efficiency of pumping equipment and the reliability of LHDs. To address these issues, an enhanced version of the conventional main drainage facility scheme, specifically designed for kimberlite mine utilizing the block caving method, is proposed. This modified scheme aims to provide improved clarification of the mine water in the water-collecting workings and facilitate more efficient dewatering of the settled slurry sludges. Furthermore, a methodology has been developed to determine the time required for slurry sludge removal, the sedimentation characteristics of the solid phase, and the rheological properties of the liquid phase of the mine water.